2022
DOI: 10.1155/2022/9476021
|View full text |Cite
|
Sign up to set email alerts
|

Potato (Solanum tuberosum L.) Growth and Quality as Influenced by Inorganic Fertilizer Rates in Northwestern Ethiopia

Abstract: Potato (Solanum tuberosum L.) is an important tuber crop that is highly affected by poor soil fertility and nutrient disparities. Nutrient depletion due to intensive monocropping and poor soil management practices is a serious problem in Ethiopia, including in northwestern areas. Therefore, an experiment was conducted in the East Gojjam zone of northwestern Ethiopia to evaluate the influence of phosphorus and potassium fertilizer rates on potato tuber production. Three phosphorus levels (0, 34.5, and 69 kg/ha−… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 45 publications
(48 reference statements)
0
4
0
1
Order By: Relevance
“…Umbi dengan ukuran yang bervariasi disebabkan oleh kandungan nutrisi yang ada dalam tanah seperti kalium dan fosfor. Kedua kandungan tersebut dapat meningkatkan ukuran, berat, dan diameter umbi (Gelaye et al 2022).…”
Section: Pembahasan Variasi Morfologi Aksesi G Superbaunclassified
“…Umbi dengan ukuran yang bervariasi disebabkan oleh kandungan nutrisi yang ada dalam tanah seperti kalium dan fosfor. Kedua kandungan tersebut dapat meningkatkan ukuran, berat, dan diameter umbi (Gelaye et al 2022).…”
Section: Pembahasan Variasi Morfologi Aksesi G Superbaunclassified
“…e intra-row spacing treatments of 20, 25, 30 (national recommendation), 35, and 40 cm were used in this study. e seed tubers were weighed and categorized under five weight ranges (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)36-50 (mostly used as blanket recommendation), 51-65, 66-80, and 81-95 g), which are used as seed tuber treatments.…”
Section: Experimental Treatment and Designmentioning
confidence: 99%
“…Large tuber yield obtained from the large seed tuber in this study indicated that the large seed tubers had the potential to produce large tuber yield due to its high content of carbohydrate to feed plants. In other ways, the large tubers may also affected by soil fertility and nutrients supplement [36]. e emerged plants with large seed tubers can sufficiently compete for resources with other neighboring plants.…”
Section: Total Tuber Yieldmentioning
confidence: 99%
“…The main reasons for Ethiopia's low potato production and productivity are a scarcity of seed tubers from better potato types and illnesses. (Tekle and Tesfu, 2023;Lulu et al, 2023;Lemessa et al, 2019;Gelaye et al, 2022). Hence, substituting local varieties by the improved potato varieties which are disease tolerant are needed to feed the increasing human population and maintain food security within short period of time.…”
Section: Introductionmentioning
confidence: 99%